Internalizing Taqwa in Islamic Religious Education - Muhammad Hanif Alatas (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Islamic Religious Education (IRE) faces a persistent challenge in bridging the gap between normative religious knowledge and its internalization into students’ lived moral and spiritual practices. Although taqwa is frequently emphasized as a central objective of Islamic education, it is often treated as a doctrinal concept rather than as an internalized ethical orientation. This study aims to reconstruct the conceptual and pedagogical foundations of taqwa through a textual–conceptual analysis of An-Naṣā’iḥ ad-Dīniyyah by Abdullah bin Alawi al-Haddad and to examine its relevance for Islamic Religious Education. Employing a qualitative library research design with thematic content analysis, the study analyzes key passages related to moral discipline, spiritual awareness, and ethical conduct. The findings indicate that taqwa functions as the core foundation of Islamic moral education, integrating belief, intention, and behavior within a framework of inner divine consciousness. The text portrays taqwa as an internalized value cultivated through moral exhortation, reflective remembrance, and gradual self-discipline rather than external compliance. These mechanisms highlight the affective and spiritual dimensions of Islamic pedagogy and align with the broader objectives of holistic character formation. The study contributes theoretically by deepening the conceptual understanding of taqwa, pedagogically by clarifying its internalization process, and academically by bridging classical Islamic ethical thought with contemporary educational discourse.